BD algebras and group cohomology - Todea, Constantin-Cosmin (Comptes Rendus. Mathématique, 2021)
BD algebras (Beilinson–Drinfeld algebras) are algebraic structures which are defined similarly to BV algebras (Batalin–Vilkovisky algebras). The equation defining the BD operator has the same structure as the equation for BV algebras, but the BD operator is increasing with degree +1. We obtain methods of constructing BD algebras in the context of group cohomology.